DETEKSI DOPAMIN SECARA VOLTAMETRI MENGGUNAKAN ELEKTRODA PASTA KARBON TERMODIFIKASI ETER MAHKOTA (DIBENZO-18-CROWN-6) - Irdawati Irdawati; Manuntun Manurung; Kadek Adi Septiawan (JURNAL KIMIA MULAWARMAN, 2015)
The research about the detection of dopamine by voltammetry method using crown ether modified carbon paste electrode has been carried out. The aims of this research are to investigate the influence of pH and the composition of modifier to the sensitivity and limit of detection for dopamine analysis. The measurement was conducted by differential pulse voltammetry method.The optimum of pH and modifier (crown ether) composition in the detection of dopamine are 4,0 and 0.8%, respectively. The linear concentration range is obtained from 10 to 200 µM, linear regression equation y = 4,968 + 0,068x with R2 = 0,9988 and limit of detection 6,865 x 10-6 M. The modified carbon paste electrode has relative standard deviation smaller than Horwitz’s (1,28%<5,66%), therefore this electrode has a good reproducibility. The recovery using crown ether-modified carbon paste electrode is 99,0% showing a good accuration. The measurement of commercial samples contain dopamine HCl (Giulini and Proinfark injection) is 87,0% and 91,5% compared with the composition on the label